Efficacy and safety of mycophenolate mofetil in patients with virus-negative lymphocytic myocarditis: A prospective cohort study. Issue 106 (January 2020) - De Luca, Giacomo; Campochiaro, Corrado; Sartorelli, Silvia; Peretto, Giovanni; Sala, Simone; Palmisano, Anna; Esposito, Antonio; Candela, Caterina; Basso, Cristina; Rizzo, Stefania; Thiene, Gaetano; Della Bella, Paolo; et al.
Abstract: Background: virus-negative lymphocytic myocarditis (VNLM) is a severe inflammatory heart disease with elusive therapies. We aimed to assess the efficacy of mycophenolate-mofetil (MMF) in patients with VNLM. Methods: patients were enrolled in this prospective cohort study and were treated with MMF, as the initial treatment in case of concomitant systemic immune diseases (SIDs), or as rescue therapy in isolated myocarditis intolerant/resistant to azathioprine. All were initially evaluated for endomyocardial biopsy; ECG, 24-h Holter, echocardiography, troponin T and NT-proBNP were obtained in all patients at baseline and after 6 months. The primary end-point was the change in left-ventricular ejection-fraction (LVEF) on echocardiogram after 6 months. Secondary outcomes: decrease in serum NT-proBNP and troponin-T levels, reduction of LV end-diastolic-volume (LVEDV), amelioration of regional wall motion abnormalities (RWMA), and modification of clinical status. Results: 20 patients (10 females, median age at diagnosis 32 [41–59] years) were enrolled. Baseline echocardiography revealed a reduced LVEF (<55%) in 11 patients (55%) and a median LV-EF of 53.5 [44–60.5]%. Baseline median troponin T and NT-proBNP were 50.5 (14.4–288.5)ng/L and 257.0 (90.5–912.0)pg/ml, respectively. After 6 months, the median LVEF significantly improved (57 [50–61]%, p = 0.016), irrespective of concomitant steroid dose. Consistently, after 6 months LVEDV decreased from 135 ± 50 ml to 114 ± 38 ml (p < 0.001), and only 6 patients had RWMA, compared to 14 at baseline (p = 0.016). The amelioration of cardiac function was paralleled by a reduction of median troponin T (12.0 [10.0–24.0], p = 0.02) and NT-proBNP(79.5 [74.5-223-2], p = 0.007) and by a reduction in the number of patients with dyspnea NYHA class II-III(p = 0.02). None of the patients required drug discontinuation. Conclusions: MMF migh be a safe and effective therapeutic option in VNLM, both as first-line agent and as a rescue therapy. Highlights: Virus-negative myocarditis is a severe heart disease with elusive therapies. Mycophenolate improves left ventricular function and reduces cardiac biomarkers. Mycophenolate might be safe and effective in treating virus-negative myocarditis. Mycophenolate is effective both as first-line agent and as rescue therapy. Mycophenolate could be part of the portfolio of treatments for virus-negative myocarditis.